PELATIHAN DESAIN PRODUK KERAJINAN KERAMIK DENGAN MENERAPKAN SOFTWARE AUTODESK INVENTOR - Sanny Andjar Sari; Reiny Ditta Myrtanti; Julianus Hutabarat; Harimbi Setyawati; Sri Indriani (Universitas Al-Falah As-Sunniyah Kencong Jember, 2026)
The Dinikoe ceramic industry faces challenges in its product design development process; designs are currently created manually, resulting in lengthy development times, limited design variations, and a lack of standardized working drawing documentation. This community service initiative aims to enhance the capabilities of the industry's personnel in developing ceramic product designs using Computer-Aided Design (CAD) software, specifically Autodesk Inventor. The methodology employed involved observation, interviews, the development of training modules, formal training, hands-on practice, mentoring, and evaluation involving six Dinikoe employees. Evaluation was conducted by comparing participants' skills before and after the training, based on indicators such as understanding product design concepts, proficiency in using Autodesk Inventor, product visualization, working drawing documentation, design variety, and dimensional accuracy. The results demonstrate an improvement in participants' competence in creating 3D models, generating digital technical drawings, and developing more innovative and accurate product design variations. The implementation of Autodesk Inventor also supports a more systematic product development process, increases design efficiency, and strengthens the MSME's competitiveness through the digitalization of design workflows. Future activities are recommended to focus on training for advanced Autodesk Inventor features, integrating design outputs with digital marketing strategies, and continuously evaluating the impact on productivity, product innovation, and business performance.